Using scenarios to assess the future supply of NHS nursing staff in England - Buchan James; Seccombe Ian (BMC, 2012)
Abstract This paper examines issues related to the future supply of registered nursing staff, midwives and health visitors in the National Health Service (NHS) in England at a time when there are major public sector funding constraints and as more of these staff are reaching retirement age. Based on available workforce data, the paper reviews different possible scenarios for the supply of NHS nurses over a ten year period, assessing the impact of different numbers of new staff being trained and of varying retirement patterns from the ageing profession. The government in England has more policy levers available than is the case in many other countries. It determines the number of pre-registration training places that are commissioned and funded, it is the major employer, and it also controls the inflow of nurses from other countries through migration policies. Scenario models provide a picture of what the future might look like under various assumptions. These outcomes can be quantified and the results used to assess the risks and opportunities of alternate policy decisions. The approach used in this paper is that of the aggregate deterministic supply model. As part of this exercise, eight scenarios were selected and modelled. These were: A. "No change"- current inflows and outflows B. "Redundancies" - current inflow with higher outflow C. "Improved retention" - current inflow with lower outflow D. "Reduced training intakes A" - lower inflows with lower outflow E. "Reduced training intakes B" - lower inflow with higher outflows F. "Pension time-bomb"- current inflow with a higher rate of retirement G. "Pension delayed"- current inflow with a lower rate of retirement H. "Worst case" - lower inflow and higher outflow including higher retirement Most of the scenarios indicate that a reduction in the supply of nursing staff to NHS England is possible over the next ten years. Small changes in assumptions can make a substantial difference to outcomes and therefore emphasize the point that it is unwise to base policy decisions on a single projection. It is important that different scenarios are considered that may be regarded as possible futures, based on a realistic assessment of the available workforce data, policies and broader labour market and funding outlook.